QS3: CRISPR/Cas9 Editing of Autologous Dendritic Cells to Enhance Angiogenesis and Wound Healing. (July 2021) - Henn, Dominic; Zhao, Dehua; Bonham, Clark A.; Chen, Kellen; Greco, Autumn H.; Padmanabhan, Jagannath; Trotsyuk, Artem A.; Barrera, Janos A.; Januszyk, Michael; Stanley Qi, Lei; Gurtner, Geoffrey C.
Abstract : Purpose: Dendritic cells (DCs) are a heterogeneous cell population which critically regulates the adaptive immune response. Depending on their activation status, DCs can also promote peripheral immune tolerance, thus limiting the activation of the immune system and tissue damage. The N-myc downregulated gene 2 (Ndrg2) is highly expressed in DCs and limits the secretion of vascular endothelial growth factor (VEGF), which is critical for wound healing. Cell based therapy approaches using DCs have been approved by the FDA and clinical trials using DC immunotherapy are being performed against a variety of cancer types. However, the role of DC therapy for wound healing has not yet been investigated. Methods: Hematopoietic progenitor cells were isolated from the bone marrow of mice and differentiated into DCs over a 7-day in vitro culture period. Pharmacologic down-regulation of Ndrg2 was performed by treatment of cultures with 1, 25-dihydroxyvitamin D3 (VD3) and the angiogenic potential of the treated cells was evaluated by endothelial cell (EC) tube formation assays. Cytokine secretion of DCs was measured in the conditioned media using Luminex multiplex assays. To permanently knock out Ndrg2 in DCs, a CRISPR/Cas9 gene editing approach was developed, using Cas9/sgRNA-ribonucleoproteins and electroporation. The determine the impact of genetically edited DCs on wound healing, splinted excisional wounds in C57BL6/J (wild-type) mice were treated weekly with pullulan-collagen hydrogels seeded with Ndrg2-knockout (KO) DCs, control DCs which had undergone electroporation only, or blank hydrogels. The transcriptomic impact of Ndrg2 downregulation on DC fate was evaluated by microfluidic single-cell RNA sequencing (scRNA seq) of Ndrg2-KO DCs, VD3-treated DCs and control DCs. Results: Ndrg2 down-regulation lead to a significantly stronger EC tube formation in co-cultures with VD3-treated DCs, and strongly enhanced VEGF secretion compared to untreated DCs in vitro. A CRISPR/Cas9 editing pipeline was developed for KO of Ndrg2 in DCs with a transfection rate and editing efficiency of > 90% shown by Sanger Sequencing. Excisional wounds treated with Ndrg2-KO DCs demonstrated significantly accelerated healing compared to control DCs and blank hydrogels. scRNA seq revealed that Ndrg2 downregulation strongly induced Vegfa expression and anti-oxidant transcriptomic signatures. Conclusion: Our data indicate that KO of Ndrg2 in DCs strongly enhances their secretion of VEGF, thus promoting angiogenesis and accelerating wound healing. Given the ready availability of DCs from the human blood through established leukapheresis protocols and easy multiplication in vitro, CRISPR/Cas9 editing of DCs is a promising new approach to induce wound healing and soft-tissue regeneration.